2020
DOI: 10.3310/hta24540
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted training compared with an enhanced upper limb therapy programme and with usual care for upper limb functional limitation after stroke: the RATULS three-group RCT

Abstract: Background Loss of arm function is common after stroke. Robot-assisted training may improve arm outcomes. Objective The objectives were to determine the clinical effectiveness and cost-effectiveness of robot-assisted training, compared with an enhanced upper limb therapy programme and with usual care. Design This was a pragmatic, observer-blind, multicentre r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 135 publications
0
35
0
1
Order By: Relevance
“…8,11 Since the first use of MIT-MANUS in the clinical environment in 1994, robotic-assisted therapy has entered a new era 12,13 and several upper limb rehabilitation robots have been developed including the Mirror Image Motion Enable (MIME) and Automatic Recovery Arm Motility Integrated System (ARAMIS). [14][15][16][17][18] However, the evidence of the effectiveness of robotic-assisted therapy is mixed 17,18 and they have not as yet been widely adopted into clinical practice. One reason for this may be the logistics of their use.…”
Section: Introductionmentioning
confidence: 99%
“…8,11 Since the first use of MIT-MANUS in the clinical environment in 1994, robotic-assisted therapy has entered a new era 12,13 and several upper limb rehabilitation robots have been developed including the Mirror Image Motion Enable (MIME) and Automatic Recovery Arm Motility Integrated System (ARAMIS). [14][15][16][17][18] However, the evidence of the effectiveness of robotic-assisted therapy is mixed 17,18 and they have not as yet been widely adopted into clinical practice. One reason for this may be the logistics of their use.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of these devices can help the familiarization of poststroke survivors with the latter technology (60). However, a decrease in upper limb impairment does not always correlate to practical and daily functional improvement and this translational aspect needs to be studied for effective neurorehabilitation (61). In fact, the wide multicenter trial for the evaluation of robot-assisted training for the upper limb after stroke (RATULS) has demonstrated that robotic neurorehabilitation does not significantly improve the upper limb function (62).…”
Section: Discussionmentioning
confidence: 99%
“…Robotic rehabilitation opens up a new way in stroke rehabilitation ( Hesse et al, 2003 ; Lambercy et al, 2011 ; Rodgers et al, 2020 ). RAT uses robot equipment to treat neurological injury and assist in post-stroke rehabilitation.…”
Section: Robot-assisted Therapymentioning
confidence: 99%